Italianizing Italy: Dubbing Woody Allen’s ’To Rome with Love’ - Franceschi, Valeria; Corrizzato, Sara (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Audiovisual translation has recently established itself within the field of Translation Studies, due to the implications of adapting a movie or TV series for an audience located in a different linguacultural context. Sociocultural and linguistic interferences may hinder the comprehension and successful fruition of the product by the target audience. As a consequence, translators often have to operate choices to work within the constraints laid by the need to familiarize the viewers with the original product. The Woody Allen movie To Rome with Love is an especially relevant example of script adaptation as it is set in the Italian capital, which implicates a strong connection with the sociocultural context of the location. Adaptation of the movie into Italian, therefore, occurs on two different, intertwining levels. On the one hand, translators have to remain faithful to the original script, and on the other, they are supposed to give a target-oriented translation that might not correspond with the representation of the country provided by the screenwriters. In this paper, we will present a comparative analysis of the English and Italian scripts aimed at identifying the strategies adopted to minimize Anglo-American interferences in the target product.